2009
DOI: 10.1093/jac/dkn545
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in vitro effects of amoxicillin and ampicillin on the polymorphonuclear neutrophil respiratory burst

Abstract: This amoxicillin pro-oxidative effect could be due to the activation of the PMN NADPH oxidase, to its induction by a membrane effect or via the OZ pathway. It probably reinforces amoxicillin intrinsic bactericidal action and might partly explain the severe rashes sometimes occurring with amoxicillin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Similarly, a previous study has demonstrated that ampicillin and carbenicillin were both unable to induce MN formation in in vivo rat bone marrow assay [Stemp et al, 1989]. AMO is structurally different from ampicillin by the addition of a hydroxyl to the amino-benzyl group of its side chain [Reynaert et al, 2009]. However, this difference does not lead to a significant distinction between the genotoxic potential of these analogs.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, a previous study has demonstrated that ampicillin and carbenicillin were both unable to induce MN formation in in vivo rat bone marrow assay [Stemp et al, 1989]. AMO is structurally different from ampicillin by the addition of a hydroxyl to the amino-benzyl group of its side chain [Reynaert et al, 2009]. However, this difference does not lead to a significant distinction between the genotoxic potential of these analogs.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies on DNA repair kinetics have shown that 5 mM AMO concentration which is far higher than the expected human clinical exposure levels was able to induce DNA single-strand breaks via oxidative mechanisms (ROS) in human peripheral lymphocytes; however, concentrations lower than 5 mM hardly evoked any effect in the same experimental design [Arabski et al, 2005;Li et al, 2007]. Furthermore, AMO has been shown to induce the production of the superoxide (O 2 2 ) radicals in polymorphic nuclear neutrophils in the absence of a metabolic activation [Reynaert et al, 2009]. On the other hand, AMO was negative in Green Screen Assay (GSA) [Cahill et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…While most classes of antibiotics do not affect neutrophil function (e.g., beta-lactams, fluoroquinolones [11][12][13]) it has been shown for some classes of antibiotics that they may affect ROS production. Among the substance classes identified are sulfonamides (sulfa drugs), which have been demonstrated to impede the respiratory burst of neutrophils [14,15].…”
Section: Introductionmentioning
confidence: 99%